Intelligence Design Of Robotic Soccer Team - Yeoh, Boon Chuan (2006)
Designing the algorithm of an intelligent robotic soccer team is challenging research domain, because the team's performance depends significantly on issues that arise solely from the interaction among agents. Robotic soccer simulation studies from experiments illustrate that the robotic agents learned policies that significantly out-performed a range of benchmark policies, and the integration of MMQL technique can highly improve the learned policies.